Comparing shopper characteristics by online grocery ordering use among households in low-income communities in Maine. Issue 15 (25th October 2021) - Zatz, Laura Y; Moran, Alyssa J; Franckle, Rebecca L; Block, Jason P; Hou, Tao; Blue, Dan; Greene, Julie C; Gortmaker, Steven; Bleich, Sara N; Polacsek, Michele; Thorndike, Anne N; Mande, Jerold R; et al.
Abstract: Objective: Online grocery shopping could improve access to healthy food, but it may not be equally accessible to all populations – especially those at higher risk for food insecurity. The current study aimed to compare the socio-demographic characteristics of families who ordered groceries online v . those who only shopped in-store. Design: We analysed enrollment survey and 44 weeks of individually linked grocery transaction data. We used univariate χ 2 and t -tests and logistic regression to assess differences in socio-demographic characteristics between households that only shopped in-store and those that shopped online with curbside pickup (online only or online and in-store). Setting: Two Maine supermarkets. Participants: 863 parents or caregivers of children under 18 years old enrolled in two fruit and vegetable incentive trials. Results: Participants had a total of 32 757 transactions. In univariate assessments, online shoppers had higher incomes ( P < 0 0001), were less likely to participate in Special Supplemental Nutrition Program for Women, Infants, and Children or Supplemental Nutrition Assistance Program (SNAP; P < 0 0001) and were more likely to be female ( P = 0·04). Most online shoppers were 30–39 years old, and few were 50 years or older ( P = 0·003). After controlling for age, gender, race/ethnicity, number of children, number of adults, income and SNAP participation, female primary shoppers (OR = 2·75, P = 0·003), number of children (OR = 1·27, P = 0·04) and income (OR = 3·91 for 186–300 % federal poverty line (FPL) and OR = 6·92 for >300 % FPL, P < 0·0001) were significantly associated with likelihood of shopping online. Conclusions: In the current study of Maine families, low-income shoppers were significantly less likely to utilise online grocery ordering with curbside pickup. Future studies could focus on elucidating barriers and developing strategies to improve access.